2021
DOI: 10.1371/journal.pone.0255597
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of gait trajectories based on the Long Short Term Memory neural networks

Abstract: The forecasting of lower limb trajectories can improve the operation of assistive devices and minimise the risk of tripping and balance loss. The aim of this work was to examine four Long Short Term Memory (LSTM) neural network architectures (Vanilla, Stacked, Bidirectional and Autoencoders) in predicting the future trajectories of lower limb kinematics, i.e. Angular Velocity (AV) and Linear Acceleration (LA). Kinematics data of foot, shank and thigh (LA and AV) were collected from 13 male and 3 female partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…In order to classify the lifting motion, the following three machine learning techniques commonly used as classification models in previous studies [32,33] were used: ANN, Support Vector Machine (SVM), Random Forest (RF). The LSTM model showing relatively high performance on a time-series data set [34][35][36][37] was used as a regression model for predicting joint moment. Figure 1 presents the structure of the proposed architecture and the overall flow chart to predict lower extremities and L5/S1 moments on sagittal plane.…”
Section: Neural Network Architecturementioning
confidence: 99%
“…In order to classify the lifting motion, the following three machine learning techniques commonly used as classification models in previous studies [32,33] were used: ANN, Support Vector Machine (SVM), Random Forest (RF). The LSTM model showing relatively high performance on a time-series data set [34][35][36][37] was used as a regression model for predicting joint moment. Figure 1 presents the structure of the proposed architecture and the overall flow chart to predict lower extremities and L5/S1 moments on sagittal plane.…”
Section: Neural Network Architecturementioning
confidence: 99%
“…From Figure 2 , only simple mathematical operations are performed to update the memory cell in each LSTM cell. The LSTM layers can be stacked to have the means for finely extracting intermediate features and finding temporal patterns from low-level input features ( Zaroug et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that the LSTM model showed an improved performance over linear regression and also Dense Neural Networks (DNN) for an ankle angle prediction task. Zaroug et al (2021) investigated the applicability of LSTM for the prediction of angular velocity and linear acceleration in the sagittal plane of thigh, shank and foot segments. Inspired by the Sequence to Sequence (Seq2Seq) model in the Natural Language Process (NLP) field, they adopted a two stage Encoder-Decoder LSTM model ( Zaroug et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, new technologies such as artificial intelligence (AI), along with biosignal processing and neural technology, will be extremely important for the development of future exoskeleton research [ 249 ]. Thanks to corrective and predictive machine learning algorithms [ 216 , 250 ], IMU sensors seem to be a very promising replacement for a wide range of physical sensors such as FSRs, pressure insoles, footswitches, potentiometers, and encoders, as they are shown to be capable of both detecting the gait phases and measuring the limb orientation and movement. The magnetometer and accelerometer components in IMU sensors might also become useful in the near future for evaluating muscle activities without EMG electrodes [ 251 ].…”
Section: Towards Fully Autonomous Portable Paesmentioning
confidence: 99%